Lumbar puncture complicated by spinal epidural hematoma in a child with leukemia. Issue 6 (9th April 2015) - Hatzipantelis, Emmanuel; Kyriakidis, Ioannis; Pavlou, Evangelos; Pavlidou, Efterpi; Stamou, Maria; Foroglou, Nikolaos; Papageorgiou, Theodotis; Hatzistilianou, Maria
Key Clinical Message We report a case of spinal epidural hematoma (SEH) preceded by diagnostic lumbar puncture (LP) in a 5‐year‐old boy with acute lymphoblastic leukemia. MRI confirmed the presence of SEH between T7 and L5 levels, but the patient showed fast recovery during the next hours and conservative management was elected.